Anti-oxidative-initiated cognitive impairment amelioration in Alzheimer's disease model rats through preventive transcutaneous electrical acupoint stimulation - Heng Weng; Qing Wang; Ran Ye; Yamei Bai; Hui Yang; Guihua Xu; Qiuqin Wang (Integrative Medicine Research)
Background: Alzheimer's disease (AD) is a chronic and irreversible neurodegenerative disease. Oxidative stress emerges at the early AD stage. As a non-invasive therapy with few adverse reactions, transcutaneous electrical acupoint stimulation (TEAS) combines acupuncture points of traditional Chinese medicine (TCM) and electrical stimulation. This study aimed to investigate the amelioration effects of preventive TEAS treatment (P-TEAS) on cognitive impairment and oxidative stress in AD model rats. Methods: The AD model was established via subcutaneous injections of D-galactose (D-gal, 120 mg/kg/d) into the back of neck for 9 weeks in Sprague Dawley (SD) rats to simulate the oxidative stress in the early AD stage. On the first day of the 10th week, Aβ1–42 (1 μg/μl) was injected into the CA1 regions of the bilateral hippocampus. P-TEAS was synchronized from the first day of subcutaneous D-gal injections for 9 weeks. Results: Empirical measurements showed that P-TEAS can improve the spatial memory ability of AD model rats in the Morris water maze. Superoxide dismutase (SOD) was upregulated in the P-TEAS group. Through the detection of the anti-oxidative stress signaling pathway, namely, Kelch-like ECH-associated protein 1 (Keap1)/ NFE2-related factor 2 (Nrf2), it was found that P-TEAS could promote Nrf2 entering into the nucleus and upregulating the production of protective factors heme oxygenase 1 (HO-1) and NADPH quinone oxidoreductase 1 (NQO1). It was also found that P-TEAS could downregulate the expressions of BCL2-associated X-protein (Bax), caspase 3, and caspase 9 to inhibit neuronal apoptosis. Conclusions: P-TEAS has similar efficacy to electroacupuncture in preventing AD occurrence and development. P-TEAS is a new non-invasive intervention therapy for the prevention of AD.